Value-Creation Model in Digital Banking Based on Qualitative Analysis - Amini , Nejat; Asayesh , Farzad; Rousta, Alireza (Business, Marketing, and Finance Open, 2025)
Digital banking generally offers lower costs compared to traditional banking systems and provides better value to society with greater speed. The present study aims to propose a value-creation model in digital banking. The research method is qualitative in nature. The statistical population in the qualitative section included 15 university professors, managers, and experts in digital banking, who were selected using a purposive sampling method. The data collection tool for the qualitative section was a semi-structured interview, and the reliability of the qualitative section was confirmed using Cohen’s Kappa coefficient. Data were analyzed using thematic analysis. The results of the thematic analysis revealed 292 codes and 64 themes, categorized into 18 basic themes and 4 organizing themes. The identified dimensions include customer digital experience management, which encompasses user-friendly design, ease of use, creating a unique experience, monitoring the digital customer experience, and utilizing technology in experience management. Digital co-creation includes direct digital feedback, indirect digital feedback, customer digital participation, and digital interaction with customers. Digital service management involves digital service customization, management of digital concerns, service delivery management, service quality improvement, diversity of digital services, customer support and training, and a value-creation digital mindset. Digital value management includes monetary value, non-monetary value, informational value, relational value, and hedonic value. Delivering digital banking services with a focus on improving accessibility, speed, and added value contributes to enhancing customer experience and strengthening digital relationships. Additionally, considering cost-value trade-offs, along with providing rewards and incentives, can further motivate customers to use digital banking services. Ultimately, creating an efficient and enjoyable customer experience plays a key role in the success of digital banking services.